Existentials and locatives in Romance dialects of Italy - Bentley, Delia; Ciconte, Francesco Maria; Cruschina, Silvio (New York : Oxford University Press, 2015)
This publication provides a large-scale comparative treatment of'there' sentences (there copula NP), reporting the results of a survey of over 100 Italo-Romance and Sardinian dialects spoken in Italy. It addresses key issues in linguistic theory and offers a valuable source of data for research on the Romance languages.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 8, 2015).
Keywords: Italian language -- Dialects -- Existential constructions; Italian language -- Dialects -- Locative constructions